139k views
1 vote
Can someone tell me this answer please and if your a tutor I need a lil help

Can someone tell me this answer please and if your a tutor I need a lil help-example-1
User Barfoon
by
5.2k points

1 Answer

4 votes

we have the expression


-9(2)/(7)-(-10(3)/(7))

step 1

Remove the parenthesis


-9(2)/(7)-(-10(3)/(7))=-9(2)/(7)+10(3)/(7)

step 2

Convert mixed number to an improper fraction

so

9 2/7=9+2/7=(7*9+2)/7=65/7

10 3/7=10+3/7=(7*10+3)/7=73/7

step 3

substitute in the expression above


-9(2)/(7)+10(3)/(7)=-(65)/(7)+(73)/(7)=(8)/(7)

step 4

Convert to mixed number

8/7=7/7+1/7=1+1/7=1 1/7

answer is option B

Step-by-step explanation

If you have a mixed number

example

9 2/7 -------> is the same that 9+2/7

To adds 9 and 2/7 -----> multiply 9 by 7/7------> 9*7/7=63/7

now the two numbers have the same denominator

63/7+2/7=(63+2)/7------> 65/7

10 3/7 -----> 10+3/7

to adds 10 and 3/7 ------> multiply 10 by 7/7 -----> 10*7/7=70/7

70/7+3/7=73/7

User Christoph Rieke
by
4.7k points